Longitudinal survey of depressive symptoms among university students during the COVID-19 pandemic in Japan - Nomura, Kyoko; Yamazaki, Teiichiro; Maeda, Eri; Hirayama, Junko; Ono, Kyoichi; Fushimi, Masahito; Mishima, Kazuo; Yamamoto, Fumio (Frontiers in Psychology, 2022)
While changes in response to the different stages of the pandemic remain unknown, this study investigated the longitudinal impact of the COVID-19 pandemic on depressive symptoms in Japanese university students and identified factors associated with new onset of depression and suicidal ideation. Two surveys were conducted at one university in Akita, Japan, during the first COVID-19 outbreak period (T1: May–June 2020) and 1 year later (T2: March–May 2021). Moderate depressive symptoms were defined as a Patient Health Questionnaire-9 score ≥ 10 and suicide-related ideation score ≥ 1 on question 9 of the questionnaire. Among 985 students who completed surveys in T1 and T2, participants with moderate depressive symptoms and suicide-related ideation increased from 11 to 17% and from 5.8 to 11.8%, respectively. Among 872 students at risk after excluding those with moderate depressive symptoms at T1, 103 students (11.8%) developed moderate depressive symptoms at T2. Among the 928 students at risk, after excluding those who had suicidal ideation at T1, 79 (8.5%) developed suicidal ideation. Multivariate logistic modeling revealed financial insecurity and academic performance as risk factors (ps < 0.01), while having someone to consult about worries was a coping factor for depressive symptoms and suicidal ideation (ps < 0.001). Our findings demonstrated that socioenvironmental factors may determine depressive symptoms of university students.